The Ability of Indonesian EFL Learners in Writing Academic Papers - Husin, M. Said; Nurbayani, Etty (IAIN Samarinda, 2017)
This study is meant to examine the thesis quality of students of English Department at IAIN Samarinda. Through the descriptive-quantitative research, the thesis quality of students of English Department at IAIN Samarinda is reviewed from the aspects of language, structure, concepts understanding, theoretical framework, methodology, content, writing mechanism, and references used. This study also tries to figure out any factors that affect the thesis quality of English Department students. Fourteen English Department Students’ thesis tested in 2013 are used as the main data. In addition, other data are obtained from respondents i.e. 19 students, and informants i.e. lecturers of English Department who are also their thesis advisors. The result shows that the average score of thesis written by 14 English Department students at IAIN Samarinda academic year of 2013 is 3.16 which is in the range of 2.61-3.40 scale, which is quite good quality. This quality is relevant with the informants’ perceptions about the quality of thesis written by their students. Judging from some aspects, they assume that their students are able to write a good quality of thesis with an average score of 2.81 which is at a scale of 2.61-3.40. The quality is affected by internal factors and external factors. The most decisive internal factor is the respondents’ low score of writing with appropriate and acceptable structure in English. This is the effect of respondents’ lack of ability of composing adequate paragraphs in English. Meanwhile, the most concerning external factor is the quality of learning structure course and the professionalism of the informants in guiding the students to improve their writing ability in thesis writing.